Overexpression of Hypermethylated Homeobox A11 (HOXA11) Inhibits Tumor Cell Growth and Induces Apoptosis in Cervical Cancer - Lee, Seung-Yul; Oh, Tae Jeong; An, Sungwhan; Lee, Seung-Hoon (Balsaeng'gwa saengsig, 2024)
This study aimed to elucidate the potential of Homeobox A11 (HOXA11) as a therapeutic target and a diagnostic methylation marker for cervical cancer. Gene expression analysis using cDNA microarray in cervical cancer cell lines revealed significantly reduced expression of the HOXA11 gene. Subsequent investigation of HOXA11 promoter methylation in samples from normal individuals and invasive cervical cancer patients showed over 53.2% higher methylation in cancer scrapes compared to normal scrapes. Furthermore, overexpression of HOXA11, which is downregulated in cervical cancer, strongly suppressed cell growth in cervical cancer cell lines, HeLa and HT3. Additionally, we performed transferase dUTP nick end labeling assay and confirmed that the inhibition of cervical cancer cell proliferation occurred via apoptosis. Mechanistically, overexpression of HOXA11 led to mitochondrial apoptosis characterized by PARP cleavage due to increased c-Myc and enhanced cytochrome C secretion into the cytoplasm. These findings suggest that HOXA11 could potentially serve as a methylation marker for diagnosing cervical cancer and as a novel therapeutic target for its treatment.